Hubungan Ketahanan Pangan Keluarga dengan Asupan Karbohidrat pada Wanita Usia Subur di Kecamatan Selo, Boyolali - Hilda Deliana; Luluk Ria Rakhma; Listyani Hidayati (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Household food security is an important factor influencing nutrient intake, including carbohydrate intake as the main source of energy. This study aimed to determine the relationship between household food security and carbohydrate intake among women of reproductive age in Selo District, Boyolali. This research used an analytic observational design with a cross-sectional approach involving 108 respondents selected using simple random sampling. Household food security was measured using the Household Food Insecurity Access Scale (HFIAS), while carbohydrate intake was assessed using a Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). Data were analyzed using the Spearman Rank test. The results showed that the majority of respondents were classified as food insecure (59.3%), with carbohydrate intake predominantly in the excessive (46.3%) and normal (38.9%) categories. Statistical analysis revealed a significant relationship between household food security and carbohydrate intake (p = 0.030) with a weak negative correlation (r = -0.209). It can be concluded that higher levels of food insecurity are associated with lower carbohydrate intake.